(3OjhGf GdJdYaQjs - (3GdJdYaQj , eMeO Hf jhSa Hf eSYhO GdTjHGfj, TgGH GdOjf CHh YHO Gddg,J (B675 (3g` s
(3ChdgG (B:s
(3de CRd ecKQkG Ydjg GdSDGdG hLhGHG eG YfOg Shi dG s
(3BNQgG (B:s
(3JYWa GdJjg efc ZVG WdjMGfG bdG JMag cKjHG egjdG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B25s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs